2001
DOI: 10.1002/1521-401x(200112)29:6/7<399::aid-aheh399>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Ambiguous Ecological Control by Dissolved Humic Matter (DHM) and Natural Organic Matter (NOM): Trade-offs between Specific and Non-specific EffectsWe dedicate this paper to Prof. Dr. Fritz H. Frimmel on the occasion of his 60th birthday anniversary.

Abstract: Several papers report on obviously contradictory biological and ecological effects of humic substances (and NOM). For instances, growth promotion as well as growth inhibition of algae and macrophytes, promotion as well as inhibition of net‐heterotrophy in non‐eutrophic lakes, promotion as well as inhibition of reproduction of the nematode, Caenorhabditis elegans, are reported. If one takes direct effects of humic substances (and NOM) on aquatic organisms into account that are supported by increasing empirical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…DOM provides energy and carbon for microorganisms in aquatic environments. Understanding the controls on the processes of DOM uptake and metabolism enhances our understanding of aquatic food webs 8–10…”
Section: Ecological Requirements For Investigating Dom Cycling Inclumentioning
confidence: 99%
“…DOM provides energy and carbon for microorganisms in aquatic environments. Understanding the controls on the processes of DOM uptake and metabolism enhances our understanding of aquatic food webs 8–10…”
Section: Ecological Requirements For Investigating Dom Cycling Inclumentioning
confidence: 99%
“…In general, net‐heterotrophy may be caused by the promotion of heterotrophic and/or the suppression of autotrophic, processes. Consequently, the resulting community response is a trade‐off of at least two competing processes (for a mathematical model of this competition, see Steinberg & Brüggemann, 2002). Many, but not all, of the HS isolates tested so far potentially suppressed photosynthetic oxygen release (Pflugmacher et al.…”
Section: Larger‐scale Ecological Significance Of Hs and Some Remaininmentioning
confidence: 99%
“…However, a promoting effect of It is evident that DOM has modulatory effects on environmental substances and their effects on organisms; however, the direction of modulation is not uniform. In a model analysis, Steinberg and Brüggemann [53] showed that humic substances can react in seemingly opposite ways, depending on their structure and chemical characterization. In fact, the effect of organic matter is a trade-off between promotion and inhibition due to its diverse nature, and this contrasting effect appeared to be intrinsic.…”
Section: Dom Can Modulate the Toxicity Of Epfrsmentioning
confidence: 99%